Dampak Resesi Ekonomi Global Terhadap Perdagangan Aset Kripto Dan Keamanan Transaksinya Di Indonesia - Bthari Octaviani Putri; Zulkarnain Sitompul (Unram Law Review, 2023)
When the Coronavirus Disease 2019 (COVID-19) pandemic has an impact on reducing world economic growth, this condition gives benefits to the digital investment sector, one of which is the increase in crypto asset trading. The crypto asset trading sector is a digital commodity that is in great demand and is growing rapidly in society. This is because crypto asset trading does not require each investor to meet each other face to face and only requires an internet network in transactions. Throughout 2021, crypto asset trading and the number of investors who transacted almost all over the world continued to experience a significant increase, including in Indonesia. However, at the beginning of 2022, there was a conflict between Russia-Ukraine which affected the increase in commodity prices around the world. This condition then triggered inflation in several major countries, which in turn resulted in the threat of a global economic recession. This phenomenon then leads to a weakening global economy which can hinder the growth of crypto asset trading in the future. Not only that, crypto asset trading itself is also still haunted by concerns about the weak security system in investing in crypto assets which is vulnerable to the rise of various fraud cases. Therefore, regulation and facilities that are following the current needs of crypto asset trading are urgently needed to stimulate the growth of crypto assets. Actions taken by the government through the establishment of crypto asset trading regulations and supporting platforms are very important to provide business certainty and security in investing in crypto assets in Indonesia.